Posture algorithm for mobile robot based on ultrawide band. (28th July 2022) - Sun, Jing; Xie, Bin; Xiong, Wei; Zhang, Qiaolong; Zhao, Zhenyu
Inertial measurement unit or other navigation devices are used to obtain the posture information of most mobile robots based on ultrawide band. However, problems, such as zero drift, temperature drift, and error increasing with time, exist in inertial measurement unit and other navigation devices. To overcome these problems, a posture algorithm for mobile robot based on ultrawide band is proposed in this article. Real-time posture information can be obtained by the posture algorithm without using inertial measurement unit and other navigation devices. Simulated results show that the mean absolute error and root mean square error of posture angle in the global coordinate system are 0.951° and 1.169°, respectively. Both the simulated and experimental trajectories show good agreement with the ideal trajectory. The results indicate that the posture data can be obtained accurately by the posture algorithm and the accuracy can meet the requirements for most mobile robots. This article is expected to be of great guiding significance for the development of mobile robots.